KOMUNITA Magazine Website Traffic Analysis: Analisa Traffic Website Majalah KOMUNITA - Abinowi, Egi; Nurpauji, Cika Alpi; Maulana Sidiq (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
KOMUNITA Magazine is one of the means to develop higher education through various aspects. In this case, KOMUNITA is a communication and information medium that seeks to reach various communities that intersect with universities from a hierarchical perspective from various aspects. Komunita Magazine through online media in the form of a website has now undergone many changes and developments so that in this case it is necessary to conduct research to determine the effectiveness of the website. Komunita Magazine's website traffic analysis aims to determine the effectiveness of changes and website development, the authors try to conduct a study using google analytics. Google analytics can generate visitor analysis reports from the web, so the authors see effectiveness based on the number of visitors.